Graphene assembled film based conformal sensor array for submillimeter crack location and direction detection. (1st January 2023) - Guan, Huijuan; Song, Rongguo; Tong, Cong; Zhao, Xin; Yang, Yingping; He, Daping
Abstract: In this paper, a conformal CSRR derived sensor array with two resonant frequencies based on a graphene assembled film (GAF) is proposed to detect and determine the direction of submillimeter cracks on aluminum plates. The GAF sensor array consists of a microstrip line, a dielectric substrate and a reference ground with two CSRR derived resonant structures. The GAF sensor array has a high sensitivity of 270 MHz for the curved aluminum plate with a crack width of 0.2 mm. In addition, the CSRR derived resonant structure array of the GAF sensor effectively detects the direction of the crack.